A Li-In alloy anode and Nb2CTX artificial solid-electrolyte interphase for practical Li metal batteries - Lee, Seung Hun; Kim, Mun Sek; 이정훈; 류지현; DO, VAN DUNG; Lee byeong gwon; Kim, Woong; Cho, Won Il (Royal Society of Chemistry, 2022)
Lithium metal (Li) has received growing attention for use in rechargeable electrochemical cells with various types of cathode owing to its potential as a high-capacity anode. However, continuous electrochemical reactions and uncontrolled electrodeposition at the surface of the anode hinder its practical usage. Here, through the coupling of a Li-In alloy as an anode material with Nb2CTX (an MXene) as an artificial solid-electrolyte interphase (Nb2CTX Li-In), we achieved a superior cycling performance to overcome the existing problems of Li anodes. The Li diffusion behavior and the interactions between the Nb2CTX Li-In alloy anode and Li were examined using density functional theory calculations, and it was confirmed that the Nb2CTX Li-In provides high Li affinities and controls Li migration. Then, the material characteristics of the Nb2CTX ASEI and Li-In alloy were respectively analyzed, and the Li electrodeposition behavior and improved reversibility were confirmed via various electrochemical experiments. The electrochemical performances of the Nb2CTX Li-In alloy anode were evaluated paired with a LiNi0.8Co0.1Mn0.1O2 cathode (NCM811), and the capacity was stably maintained for >450 cycles. Finally, a Nb2CTX Li-In pouch cell (similar to 272 W h kg(-1), 500 W h L-1) was fabricated with a practical composition of high loading NCM811 (4.1 mA h cm(-2)) and a limited amount of electrolyte (2.4 mu L (mA h)(-1)), and was operated for >200 cycles. The Nb2CTX Li-In alloy anodes exhibit a high reversibility and stability for Li deposition and migration during the repeated cycling of lithium metal batteries.